2018
DOI: 10.1016/j.msec.2018.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of stainless steel for biomedical applications: Revisiting a century-old material

Abstract: Stainless steel (SS) has been widely used as a material for fabricating cardiovascular stents/valves, orthopedic prosthesis, and other devices and implants used in biomedicine due to its malleability and resistance to corrosion and fatigue. Despite its good mechanical properties, SS (as other metals) lacks biofunctionality. To be successfully used as a biomaterial, SS must be made resistant to the biological environment by increasing its anti-fouling properties, preventing biofilm formation (passive surface mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(109 citation statements)
references
References 117 publications
(193 reference statements)
1
106
0
2
Order By: Relevance
“…The characteristic calcium hydroxyapatite absorption bands in the range of 1100-950 cm −1 were clearly visible [32]. Strong bands located at 1035 and 1090 cm −1 resulted from the ν 1 symmetric P-O stretching vibrations in PO 4 3− [32,33]. The broad band visible in the range of 3600-3300 cm −1 is associated with O-H stretch vibrations and attributed to adsorbed water [29,32,34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic calcium hydroxyapatite absorption bands in the range of 1100-950 cm −1 were clearly visible [32]. Strong bands located at 1035 and 1090 cm −1 resulted from the ν 1 symmetric P-O stretching vibrations in PO 4 3− [32,33]. The broad band visible in the range of 3600-3300 cm −1 is associated with O-H stretch vibrations and attributed to adsorbed water [29,32,34].…”
Section: Resultsmentioning
confidence: 99%
“…Fibrous tissue formation is caused by the absorption of protein and other organic molecules on the hydrophobic surface of metals. Hydrophobic surfaces attract these organic molecules with enhanced formation of the above-mentioned biofilms [4,5]. It was suggested that formation of protein capsules may cause inflammation at the implant-bone interface, followed by the rejection of an implant [6].…”
Section: Introductionmentioning
confidence: 99%
“…SS-based bioimplants either need revision surgery or to be used as a permanent bioimplant after bioactive coating or surface modification using bioactive nanomaterials. The modification of SS with bioactive hydroxyapatite (HA) improves the osseointegration and bio-integration properties of an orthopedic bioimplant [63,83,84]. Typical applications include bone plates, medullary nails, screws, pins, sutures, and steel threads used in fixation of fractures [14,[85][86][87][88][89][90].…”
Section: Stainless Steel (Ss)mentioning
confidence: 99%
“…[4,[8][9][10][11]. To improve these disadvantages of BSSs and then enhance their surface properties and biocompatibility, various surface modification approaches were employed to alter the surface performances of BSSs [12][13][14][15][16]. Tonino et al [17] have indicated that the formation of a porous oxide layer on the surface of the 316L BSS implants can be utilized in the morphological fixation of the implants to bone through bony ingrowth into the porous microstructure.…”
Section: Introductionmentioning
confidence: 99%